Breaking bad news in spinal cord injury; a qualitative study assessing the perspective of spinal cord injury survivors in Turkey - Ozyemisci-Taskiran, Ozden (J Spinal Cord Med, 2018)
PRIOR ABSTRACT PUBLICATION: 2(nd) Medical Rehabilitation Congress; Nov 4–7, 2010; Ankara, Turkey OBJECTIVE: This study aims to investigate the process of breaking bad news from the perspective of spinal cord injury survivors. DESIGN: A cross sectional, qualitative study. SETTING: Community. PARTICIPANTS: Fourteen spinal cord injury survivors. INTERVENTIONS: Subjects participated in a semi-structured interview about ‘when’, ‘where’ ‘by whom’ and ‘how’ they received and ‘would’ prefer to receive bad news. OUTCOME MEASURES: Answers to ‘how’ questions were coded according to SPIKES protocol (Setting, Perception, Invitation, Knowledge, Empathizing, Summary). RESULTS: Eight participants (57%) reported that they received bad news from a physician, mostly during rehabilitation. All would prefer to be informed by a physician and majority preferred to be gradually informed during rehabilitation. Half were not satisfied with the content of information. Only half felt that his/her physiatrist understood his/her emotional distress. Majority of participants who received bad news from physicians reported that the setting was private and their family members accompanied them. CONCLUSION: Most spinal cord injury survivors were unsatisfied with knowledge and emotional support provided by rehabilitation physicians. Participants would prefer to receive bad news by a senior physiatrist in a planned meeting during rehabilitation.